The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1021/jp993838l
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Polarizabilities and Second Hyperpolarizabilities of Inorganic Transition Metal Thiometalates and Metalates in Solution

Abstract: A systematic study of nonlinear optical (NLO) properties of inorganic transition metal (TM) thiometalates and metalates is reported. Polarizabilities (R) and second hyperpolarizabilities (γ) are calculated in solution within the polarizable continuum model. It is found that NLO properties of anionic inorganic complexes can be successfully modeled in solution, when this cannot be done so in the gas phase. Solvent effects are found to significantly increase R and γ. The effects are stronger on γ (up to 80%) than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 31 publications
(73 reference statements)
3
10
0
Order By: Relevance
“…The continuum results are qualitatively the same as those coming from similar treatments, 8,11,55,56 i.e., all properties computed are numerically larger than their respective vacuum values. Local fields are only considered and applied in the work of Macac et al 56 but they use an expansion for the induced dipole ͓their Eqs.…”
Section: Resultssupporting
confidence: 72%
“…The continuum results are qualitatively the same as those coming from similar treatments, 8,11,55,56 i.e., all properties computed are numerically larger than their respective vacuum values. Local fields are only considered and applied in the work of Macac et al 56 but they use an expansion for the induced dipole ͓their Eqs.…”
Section: Resultssupporting
confidence: 72%
“…For studies of heavier elements, treatment of relativistic effects is necessary, at least in the form of effective core potentials 103. Transition element coordination compounds were excluded, since more sophisticated modeling with at least the first coordination shell has to be taken into account 97–100, values for closed shell metalates and thiometalates can be found in the works of Cundari et al 96, 104. More values for ions in gas or condensed phase can be found in Refs.…”
Section: Results For Gas Phase and Pcm Calculationsmentioning
confidence: 99%
“…73). For anions, this is not necessarily the case, as demonstrated in a PCM study on transition metal thiometalates and metalates 96. For metalates of charge −3 and −4, the authors found a decrease in polarizabilities which was rationalized by the unstable state of these highly charged ions in gas phase leading to relatively high gas phase polarizabilities.…”
Section: Solvation Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The usefulness and reliability of the pseudopotentials and, in particular, the large-core ones for the calculation of ͑hyper͒plarizabilities have been discussed by various authors. [19][20][21] The relativistic correction to the L&NLO properties has been estimated by employing the Douglas-Kroll approximation, 22 in connection with the HyPol basis, 17 which has been specifically developed for relativistic calculations.…”
Section: Methodsmentioning
confidence: 99%